Cyclopropane Intermediates from Insertion Reactions of Platinum–Carbenes: A Route to Heterospiranes - Kim, Kiseong; Kim, Soyung; Oh, Chang Ho (Synlett, 2018)
Heteroaromatic-anchored enynals with a pendent alkene group were successfully cyclized through a Huisgen-type [3+2] cycloaddition to give a tetracyclic Pt–carbene complex that underwent insertion into the C–H bond in the β-position to give fused cyclopropanes that are otherwise inaccessible. On heating, the cyclopropanes smoothly rearranged to form the corresponding heterospiranes with excellent levels of stereoselectivity and high yields.
Keywords: cyclization; platinum catalysis; pyrylium ions; carbenes; heterospiranes